Women in Science Commercialization: Looking for Gender Differences - Lažnjak, Jasminka (Array, 2011)
This article analyzes the participation of women in technology-oriented scientific projects (known as the TEST program) to identify gender-based differences in attitudes toward commercialization and innovation based on scientific research. The analysis is based on the TEST program that marks a milestone in science policy in Croatia, and represents a shift toward innovation policy. There is a higher representation of women project leaders in the TEST program than in the standard scientific projects. Our research started with the hypothesis that the higher pro- portion of women scientists in technology projects is related to gender differences in sociodemographic characteristics, in the motivation for application as well as implementation of the projects, and satisfaction with the results of the TEST program. The results confirmed gender differences only in scientific field, previous career positions, and num-ber of scientific publications, and do not offer an explanation of the relatively higher proportion of women researchers in TEST program. The findings indicate that once women scientists have an equal chance for commercialization, they perform as well as men do.